1997
DOI: 10.1046/j.1464-410x.1997.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary continence after radical retropubic prostatectomy. Analysis and synthesis of contributing factors: a unified concept

Abstract: Objective To assess the eÂects of three types of apicalResults Continence was achieved in 93% overall, with 90%, 93% and 99% achieving continence in Groups dissection on urinary continence after radical retropubic prostatectomy and to evaluate possible contributing 1, 2 and 3, respectively. The mean time to continence was 68 days overall, taking 100, 52 and 30 days for factors, e.g. preservation of the bladder neck and preprostatic sphincter, age, anastomotic strictures, previous the respective groups. Twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 0 publications
2
28
1
Order By: Relevance
“…In comparison, in a human infant the striated muscle comprised 79% of the urethra; with increasing age this decreased to 35.5% in an elderly man [6]. This reduction probably explains why the incidence of incontinence after prostatectomy increases with age in men [7].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In comparison, in a human infant the striated muscle comprised 79% of the urethra; with increasing age this decreased to 35.5% in an elderly man [6]. This reduction probably explains why the incidence of incontinence after prostatectomy increases with age in men [7].…”
Section: Introductionmentioning
confidence: 93%
“…In older men there is also reported to be a linear correlation between age and the amount of connective tissue [17]. It has been suggested that the smaller amount of striated muscle in older men is the morphological basis for their higher incidence of urinary incontinence after prostatectomy than in younger men [6,7]. In healthy dogs, 10 years is possibly not long enough to produce such marked changes in the urethra.…”
Section: Urethral Striated Muscle Of Male Greyhounds 345mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the bladder neck preservation was proposed to improve the continence rate after radical prostatectomy, but today there is a general agreement that the preservation of the external sphincter is the most important factor in this purpose [2]. The laparoscopic approach is superior in that way, because it combines a better vision with meticulous hemostasis, allowing for a superior sphinctersparing apical dissection.…”
Section: Discussionmentioning
confidence: 99%
“…This gathering technique should make it easier to find the urethra and to isolate the neurovascular bundles. However, no data on blood loss were provided with this potential improvement of the standard method [5,6].…”
Section: Discussionmentioning
confidence: 99%